(untitled) (Journal of Naval Architecture and Marine Engineering, 2009)
The hydrodynamic behaviour of a fast fine vessel is of great importance than that of a fuller vessel as the fast fine vessels are engaged for important operations. Moreover with the advent of modern computers, in ship hydrodynamics, 3-D source distribution method is gaining much popularity and normally applied for blocky hull. But in the case of finer hull, examples are rare especially considering forward speed effect. With these views in mind, in the present research work, effort has been given to develop a mathematical model for fine shape vessel to predict and simulate her motions in irregular waves. A computer program has been developed on the basis of mathematical model and to examine the validity of the developed program, results for hydrodynamic coefficient and motions of a series 60 ship have been compared with Gerristma’s experimental results and with the results based on other codes. After validation of the program, simulation of motions of an existing the fine shape ship has been carried out at Hiron point of the Bay of Bengal by utilizing hydrodynamic coefficients and wave exciting forces and moments obtained in regular waves and a new wave spectrum formula based on wave data at the concerned location. On the basis of the results presented, it may be concluded that the developed model based on 3-D distribution technique can be applied for prediction of motion of fine shape ship with forward speed effect. Moreover limitations of operation of the vessel have been demonstrated at various combinations of significant wave heights and speeds. doi:10.3329/jname.v2i2.1870 Â Journal of Naval Architecture and Marine Engineering 2(2005) 25-40